EFFECTIVENESS OF ACCOMPANIMENT FOR ADOLESCENTS AND PREGNANT WOMEN WITH ANEMIA: ENDEAVORS IN EARLY STUNTING SCREENING DURING THE FIRST 1000 DAYS OF LIFE - Desi, Nina Maria; Izah, Nilatul (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
The 2022 Indonesian Nutritional Status Study survey reveals that the prevalence of stunting among children under five was 21.6%. In Central Java province, the rate was 20.8%, while in Brebes Regency, it reached 29.1% (the highest in Central Java). Stunting poses a significant nutritional challenge affecting the growth and development of young children. This issue is linked to factors such as malnutrition in pregnant women, adolescents, and nursing mothers, as well as the presence of infectious diseases in mothers. The well-being of young women is crucial, as they will become the next generation of parents, shaping the nation's future. By 2030, an estimated 68% of Indonesia's economic support will come from individuals of productive age, including current adolescents who will soon become parents. This cross-sectional observational study aimed to assess the effectiveness of assisting adolescents and pregnant women with anemia as an early stunting screening initiative. The data collection involved checking hemoglobin levels in adolescents and pregnant women, assisting those with anemia for 30 days, and then re-evaluating their hemoglobin levels. Univariate frequency distribution analysis indicated increased hemoglobin levels among adolescents and anemic pregnant women. Chi-square analysis resulted in a p-value of 0.04, suggesting that assisting adolescents and pregnant women as an early stunting screening effort effectively addresses anemia.